Cross-field diffusion of energetic (100 ke V to 2 Me V) protons in interplanetary space - Costa Jr, Edio da; Tsurutani, B. T.; Alves, Maria VirgÃnia; Echer, Ezequiel; Lakhina, G. S. (My University, 2013)
Magnetic field magnitude decreases (MDs) are observed in several regions of the interplanetary medium. In this paper, we characterize MDs observed by the Ulysses spacecraft instrumentation over the solar south pole by using magnetic field data to obtain the empirical size, magnetic field MD, and frequency of occurrence distribution functions. The interaction of energetic (100 keV to 2 MeV) protons with these MDs is investigated. Charged particle and MD interactions can be described by a geometrical model allowing the calculation of the guiding center shift after each interaction. Using the distribution functions for the MD characteristics, Monte Carlo simulations are used to obtain the cross-field diffusion coefficients as a function of particle kinetic energy. It is found that the protons under consideration cross-field diffuse at a rate of up to â‰ˆ11% of the Bohm rate. The same method used in this paper can be applied to other space regions where MDs are observed, once their local features are well known.
Keywords: Magnitude decreases; Interplanetary magnetic field